Analysis of sleep status and influencing factors in patients with type 2 diabetes (2型糖尿病患者睡眠状况及其影响因素分析) - YANG Zihan (杨梓含); WANG Yunxuan (王云轩); TIAN Jiahe (田佳禾); WANG Peng (王鹏) (中西医结合护理)
Objective To investigate the sleep status of patients with type 2 diabetes and analyze the influencing factors. Methods This study is a cross-sectional study using convenience sampling method and questionnaire-based survey. The Pittsburgh Sleep Quality Index Scale (PSQI) was used to assess the sleep status of patients. Results Totally 223 patients were recruited in this study. The patient's PSQI score ranged from 0 to 16, with an average score of (4. 00±3. 10). Totally 173 (77. 58%) patients had good sleep quality, 39 (17. 49%) had average sleep quality, 10 (4. 48%) had poor sleep quality, and 1 (0. 45%) had very poor sleep quality. Univariate analysis showed that the patients' PSQI scores were higher in female patients, aged 45 years old or older, with education level of senior high school /technical secondary school or below, non-employed patients, with family monthly per-capita income 5000 RMB or less, and those who had symptoms of hypoglycemia (P<0. 05). Multivariate logistic regression analysis showed that low education level (P=0. 007) and occurrence of hypoglycemia (P=0. 016) were independent influencing factors for patients with sleep disorders. Conclusion Patients with type 2 diabetes had a higher proportion of sleep disturbances. Patients with education level of senior high school or technical secondary school education and below, and who have had hypoglycemia are more likely to have sleep disorders. (目的 调查2型糖尿病患者睡眠状况, 分析其影响因素。方法 采用横断面研究设计, 方便抽样和问卷调查法。运用匹兹堡睡眠质量指数量表(PSQI)评定患者睡眠状况。结果 本研究共收集患者223例。患者PSQI得分0～16分, 平均(4. 00±3. 10)分。173(77. 58%)例患者睡眠质量良好, 39(17. 49%)例一般, 10(4. 48%)例较差, 1(0. 45%)例很差。单因素分析显示, PSQI得分在女性、年龄≥45岁、文化程度高中/中专及以下、不工作、家庭人均月收入≤5000元人民币、出现过低血糖的患者中更高(P＜0. 05)。多因素logistic回归分析显示, 文化程度低(P=0. 007)、出现过低血糖(P=0. 016)为患者睡眠障碍独立影响因素。结论 2型糖尿病患者睡眠障碍比例较高。高中/中专及以下文化程度、出现过低血糖患者更可能出现睡眠障碍。)